An electrostatic sensor for the continuous monitoring of particulate air pollution - Panich Intra (2018)
We developed and evaluated a particulate air pollution sensor for continuous monitoring of size resolved particle number, based on unipolar corona charging and electrostatic detection of charged aerosol particles. The sensor was evaluated experimentally using combustion aerosol with particle sizes in the range between approximately 50 nm and several microns, and particle number concentrations larger than 1010particles/m3. Test results were very promising. It was demonstrated that the sensor can be used in detecting particle number concentrations in the range of about 2.02×1011and 1.03×1012particles/m3with a response of approximately 100 ms. Good agreement was found between the developed sensor and a commercially available laser particle counter in measuring ambient PM along a roadside with heavy traffic for about 2 h. The developed sensor proved particularly useful for measuring and detecting particulate air pollution, for number concentration of particles in the range of 108to 1012particles/m3. © 2013 Korean Institute of Chemical Engineers, Seoul, Korea.